Palliative Gastrectomy vs. Gastrojejunostomy for Advanced Gastric Cancer: A Systematic Review and Meta-Analysis - Lin, Chunfang; Fan, Haibo; Chen, Wenjun; Cui, Lingzhi (Frontiers in Surgery, 2021)
Background: Advanced gastric cancer is the fifth leading cause of cancer-related deaths. Patients with metastatic advanced gastric cancer commonly develop a gastric outlet obstruction that considerably worsens their quality of life. Surgical interventions such as gastrojejunostomy and palliative gastrectomy are commonly administered to alleviate this obstruction. However, whether one intervention is better than another at improving morbidity- and mortality-related outcomes is unclear. Thus, in this meta-analysis, we compare outcomes of palliative gastrectomy and gastrojejunostomy (overall hospital stay length, time to oral intake, survival, and complication rates) in patients with metastatic advanced gastric cancer to identify the best procedure. Objective: To compare morbidity and mortality outcomes of palliative gastrectomy and gastrojejunostomy in patients with metastatic advanced gastric cancer. Methods: We followed the PRISMA guidelines to systematically search Web of Science, EMBASE, CENTRAL, Scopus, and MEDLINE for relevant studies. We conducted a random-effects meta-analysis to find differential outcomes between palliative gastrectomy and gastrojejunostomy among variables such as time to oral intake, overall hospital stay length, complication rates, and survival in patients with metastatic advanced gastric cancer. Results: From 963 studies, we found 7 eligible studies with 642 patients (70.3 ± 4.7 years) who had undergone palliative gastrectomy or gastrojejunostomy. Our meta-analysis revealed an insignificant (p>0.05) differences in terms of overall survival duration (Hedge’s g, 1.22), complication risks (odds ratio, 1.35), and time to oral intake (g 0.62) and hospital stay length (g, 0.12) between patients undergoing gastrojejunostomy and palliative gastrectomy. Conclusion: In this present study we observed no statistically significant differences in terms of morbidity and mortality outcomes after palliative gastrectomy and gastrojejunostomy in patients with metastatic advanced gastric cancer. Therefore, no conclusions can be drawn for the variables evaluated. This study provides a preliminary overview of the risks associated with gastrojejunostomy and palliative gastrectomy to help gastroenterologists manage patients with metastatic advanced-stage gastric cancer.